Pemodelan Beban Pada Struktur Dermaga Multipurpose dengan SAP2000 - Budiono Joko Nugroho; Hartono Hartono (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
A wharf is a building in a port that is made to moor or close ships that will unload or load goods and unload ferries. This research focuses on modeling the multipurpose wharf structure. The structure of the Deck on Pile wharf is designed to be strong against loads that work either or from areas that include wind, waves, currents, earthquakes and loads due to activities at the pier including ship collision loads (berthing), mooring, loads and vehicles. In this study, trying to analyze on field conditions including information on hydrooceanography, topography, bathymetry, ship design information and pier design. The design of the wharf structure includes the size of the structure, analysis of the strength of structure using the SAP2000 software.